Analysis of the generation potential of hybrid solar power plants - Martins, Gleyzer; Mendoza, Oscar Saul Hernandez; Amjad, Muhammad; Bandarra Filho, Enio Pedone (Frontiers in Energy Research, 2023)
Photovoltaic solar energy has emerged in Brazil in distributed generation due to affordable costs and its application in different segments of the market. However, the electric energy storage in the photovoltaic systems is only viable for certain conditions in which the installation does not have access to the electricity network and the thermal portion of the solar energy is lost to the ambient. Heliothermic power plant represents another system available for solar electricity generation, which has higher costs, but takes better advantage of the portion of thermal energy and allows energy storage efficiently to meet the demands during periods without incident solar radiation. Heliothermic and photovoltaic generation have great potential in the Southeast and Northeast regions of Brazil, but the costs of both technologies cannot meet the demands during periods without solar radiation. This work presents a conceptual analysis of compound parabolic solar concentrators along with hybrid of photovoltaic and thermal collector systems to meet both the demand during sunlight hours and without solar radiation. The investigation consisted of implementing an organic Rankine cycle with different heliothermic plant configurations and the analysis of the diode model to examine different commercial photovoltaic cells operated in the Rankine cycle evaporation region. The results showed that the best working fluid for the application is R245fa with Urea-NaCl as molten salt for the thermal energy storage. The expected electrical power for the hydride cycle is 1580W at 2600 rpm and at 80°C of evaporation temperature, enabling a power generation for 1 hour and 20 min without solar radiation.